Mapeamento da suscetibilidade à inundação na bacia hidrográfica do ribeirão da fábrica, município de Patos de Minas - MG - Nogueira, Tallita Pereira Nakanami (2017)
The objective of this study was to analyze the morphometric characteristics and elaborate thematic maps (hypsometry, declivity, land use, and native vegetal coverage) of the Fabrica Creek, located in municipality of Patos de Minas City – MG, with focus on mapping flood susceptible areas. In order to diagnose the morphometric conditions, the area of study was divided in three sub- basins: Fabrica Creek (SBRF), Canavial Brook (SBCC) and Monjolo Brook (SBMJ). The results presented show that Fabrica Creek doesn’t have flooding tendencies, nevertheless, by analyzing the results of the average declivity and sinuosity of the water courses, the same Creek presented rectilinear format, located in a flat area, differently from its tributaries, which possess bigger declivities. This factor, combined with the urbanization and waterproofing, favor the raise of the superficial outflow and the occurrence of mid-intensity flood in that place. To obtain the flood susceptible areas map, it was integrated to ArcGIS the thematic maps, whose classes, identified in each variable, were reclassified in 0 to 10 scores, depending on the level of the flood susceptibility. To reclassify the variable regarding the land use and native vegetal coverage, an adaptation of the Flow Curve Number Method, which correlates the soil use and hydrologic response was utilized. The identification of flood susceptible areas was obtained through the application of the Analytic Hierarchy Process – AHP, proposed by Thomas L. Saaty, in which the analysis of the elements was carried out in pairs in a comparison matrix, what generated a mathematic model utilized to cross the thematic maps. This methodology enabled the elaboration of two scenarios, being considered sometimes the declivity with considerable higher importance than hypsometry (scenario 1), and sometimes the opposite (scenario 2). While analyzing the occurrences of flooding registered in the area of study, the scenario 2 represented better the space of flood susceptible areas, being divided in 05 classes: very low, low, medium, high and very high. The evaluation of scenario 2 allowed to infer that the basin has an average flood susceptibility (24,18%), being this percentage close to the high class (21,05%) and the low class (21,72%). In a lesser degree of representativeness, the classes very low and very high were identified, with this last class (18,57%) being considered as the most important for the analysis of the flooding factor. The morphometric analysis and the mapping of flood susceptible areas (classified as very high) complemented themselves, presenting a direct correlation with some areas, where some floods had occurred, mainly in urbanized and flat regions. It was verified that flood occurrences in the city council were sporadic, and that the basin has a disposition of concentrating a higher volume of water in areas with low declivity and altitudes.